How can South Africa, a resource rich and labour-abundant economy, employ upstream and downstream mineral beneficiation as a way of developing its economy further? A critical focus on the chromium mineral value chain as a case study - Bhengu, Nombuso (My University, 2016)
South Africa has been referred to as a country of “geological superlatives” because of its rich and diverse mineral resource base. Despite its unique endowment of precious metals and mineral resources, the country has fallen short of translating these resources into the required economic linkages that will lead to sustainable employment creation and economic emancipation for the majority of its people. Whilst the country has established, successful critical upstream industries based on its natural resource advantage, it has not managed to develop successful downstream value additions in most of its strategic value chains, most notably the chromium mineral value chain. This paper explores the significance of the chromium mineral value chain in the context of South Africa’s economic development trajectory, the dynamics between the mining and manufacturing sectors, the ongoing structural constraints, and the implications all these have on stainless steel fabrication. South Africa is a dominant player in chrome, consuming approximately 80% of the world’s chromite ore reserves and is undeniably one of the major producers of ferrochromium globally, with production accounting for approximately 34% of total world production. Despite a mature ferrochromium industry that boasts world-class ferrochromium manufacturing facilities and contributes massively to the domestic and global economies, a declining market share to China threatens the sector. The availability (or lack thereof) of power supply, high energy costs, uncompetitive domestic prices amongst other structural issues are contributing to this decline. The challenge remains in government, the mining industry, labour and all other affected stakeholders to engage robustly in order to preserve a value chain that possesses enough potential to enhance the development of the country, both socially and economically.
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences.
Keywords: Mineral industries--South Africa; Chromium industry--South Africa; Stainless steel industry--South Africa